AC susceptibility and electrical properties of Ag2S added Bi1.6Pb0.4Sr2CaCu2O8 superconductor - Salma, M. A.; Kechik, M. M. Awang; Lim, K. P.; Hak, R. Che; Ilhamsyah, A. B. P.; Abd-Shukor, R.; Chen, S. K. (Springer Science and Business Media Deutschland GmbH, 2025)
Bi1.6Pb0.4Sr2CaCu2O8 (Bi-2212) superconductor samples doped with silver sulfide (Ag2S) in different weight percentages (x = 0, 0.1, 0.2, 0.4, 0.5, and 1.0 wt.%) were synthesized by the solid-state reaction method. X-ray diffraction (XRD) analysis revealed that all the samples contained Bi-2212 as the dominant phase. The electrical resistance versus temperature curves showed metallic normal state behavior for samples with 0 ≤ x ≤ 0.4 while the sample with x = 0.5 wt. % and x = 1.0 wt. % showed a semimetal-like normal state behavior with an onset transition temperature, Tc onset between 82 and 96 K and zero transition temperature, Tc zero between 65 and 77 K. AC susceptibility curves showed that the susceptibility transition temperature, Tcχ’ was between 76 and 83 K for all samples. The intergrain critical current density, Jc at the peak temperature, Tp of the imaginary part of the susceptibility c” for all samples was between 16 and 19 A⋅cm− 2. The x = 0.1 wt% sample showed the highest Tp, (65 K), indicating an improvement in the flux pinning strength. The highest maximum intergrain Josephson current, I0 and Josephson energy, Ej were between 11.12 and 14.41 µA and 23.02–29.60 meV, respectively for x = 0.5 and 1.0 wt% samples. This work demonstrated that a lower amount of Ag2S improved the flux pinning energy of the Bi-2212 phase while a higher amount of Ag2S enhanced intergrain coupling.